Empirical Causality of Employee Work Productivity - Tapi Rondang Ni Bulan; Audia Junita; Ridayati Fadillah (Universitas Mercu Buana, 2022)
Objectives: This study aims to determine the relationship between superior-subordinate communication on work productivity with work enthusiasm and positive work attitudes as mediating variables at the Department of Transportation of North Sumatra Province. Methodology: This research uses associative research type with quantitative paradigm. The population and sample used in this study, namely all employees/staff at the Department of Transportation of North Sumatra Province, totaling 118 staff. The saturated sampling technique is used to determine the research sample. Path analysis research design is used as an analytical tool to determine the direct or indirect relationship, between independent and dependent variables. Descriptive statistics are also used to discuss the research findings in greater depth. Primary data were processed using IBM SPSS 23 software.Finding: The superior-subordinate communication has a positive significant impact on work productivity either directly or indirectly through work enthusiasm and positive work attitudes. The results justify the significant contribution of superior-subordinate to work enthusiasm.Conclusion: The results of research related to superior-subordinate communication relations, work enthusiasm, and positive work attitudes towards work productivity in general have shown good conditions. However, in particular, there needs to be a better improvement regarding the communication relations between superiors and subordinates, work enthusiasm, and positive work attitudes of employees to increase the work productivity of employees at the Department of Transportation of North Sumatra Province.